A representação da cidade na poesia de Bandeira, Drummond e Cora Coralina - Melo, Thaise Monteiro da Silva (2014)
The theme of this research is the city as a reference in the creation of three Brazilian poets of modernity, Manuel Bandeira, Carlos Drummond de Andrade and Cora Coralina. From this place that presents itself and its subjectivity, and the individual’s uneasiness from an objective and collective reality. Based on individual and collective’s memories and in the autobiography the poets build images of their cities and then rebuild them into words. The main objective of this research is to comprehend how the hometowns representations of our authors, Recife, Itabira, and the City of Goiás are arranged, and subsequently, to establish between them the resemblances, the confluents and the divergent relationships. In our work, we propose initially to rescue some of the lyric poetry’s theories, the image and the representation and, through the powerful lines and trends that are acquired with modernity. Then, we articulate a thought about the city and its relationship with literature, modern poetry, memory and autobiography. The city is analyzed as much as in its physical and geographical aspects, as the human, represented by those who inhabit this space. The poets choice regarding the subjects, spaces and beings that compose his poetry, related to the moment lived by them, are considered with the purpose to understand the tools and means used by Bandeira, Drummond and Cora to represent the cities where they were born, and raised during their childhoods.